2022
DOI: 10.26650/iuitfd.948137
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bladder Pain Syndrome/Interstitial Cystitis on Partner Sexual Functions

Abstract: Objective: Bladder pain syndrome/Interstitial cystitis (BPS/IC) negatively affects both women's social life and sexual functions. The study researched if this situation can negatively affect the sexual functions of the male partners of these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the study conducted in Italy at the beginning of the pandemic, it was reported that the sexual functions of the couples increased with the increase in the length of time they were together (26). It was also supported in a recent study that the effect of female sexual functions is also effective in the male partner (27). In our study, we thought that the increase in women's sexual functions is related to the fact that couples spend time together due to their low socioeconomic level.…”
Section: Discussionmentioning
confidence: 81%
“…In the study conducted in Italy at the beginning of the pandemic, it was reported that the sexual functions of the couples increased with the increase in the length of time they were together (26). It was also supported in a recent study that the effect of female sexual functions is also effective in the male partner (27). In our study, we thought that the increase in women's sexual functions is related to the fact that couples spend time together due to their low socioeconomic level.…”
Section: Discussionmentioning
confidence: 81%
“…Lower urinary tract symptoms (LUTS) are characterized by three main symptoms 1 : storage symptoms, such as urgency, frequency, nocturia, and urge incontinence 2 ; voiding symptoms, such as poor and/or intermittent stream; and 3 post-voiding symptoms, such as the feeling of incomplete emptying 5 . LUTS exceeds the critical threshold, quality of life is impaired, level of physical activity is decreased, and psychological condition is negatively affected 6 .…”
Section: Introductionmentioning
confidence: 99%